Infrared multiple photon dissociation action spectroscopy of protonated unsymmetrical dimethylhydrazine and proton-bound dimers of hydrazine and unsymmetrical dimethylhydrazine. Issue 45 (12th November 2021) - McNary, Christopher P.; Demireva, Maria; Martens, Jonathan; Berden, Giel; Oomens, Jos; Hamlow, L. A.; Rodgers, M. T.; Armentrout, P. B.
Abstract : The gas-phase structures of protonated unsymmetrical 1, 1-dimethylhydrazine (UDMH) and the proton-bound dimers of UDMH and hydrazine are examined by infrared multiple photon dissociation (IRMPD) action spectroscopy. Abstract : The gas-phase structures of protonated unsymmetrical 1, 1-dimethylhydrazine (UDMH) and the proton-bound dimers of UDMH and hydrazine are examined by infrared multiple photon dissociation (IRMPD) action spectroscopy utilizing light generated by a free electron laser and an optical parametric oscillator laser system. To identify the structures present in the experimental studies, the measured IRMPD spectra are compared to spectra calculated at the B3LYP-GD3BJ/6-311+G(d, p) level of theory. These comparisons show that protonated UDMH binds the proton at the methylated nitrogen atom (α) with two low-lying α conformers probably being populated. For (UDMH)2 H +, the proton is shared between the methylated nitrogen atoms with several low-lying α conformers likely to be populated. Higher-lying conformers of (UDMH)2 H + in which the proton is shared between α and β (unmethylated) nitrogen atoms cannot be ruled out on the basis of the IRPMD spectrum. For (N2 H4 )2 H +, there are four low-lying conformers that all reproduce the IRMPD spectrum reasonably well. As hydrazine and UDMH see usage as fuels for rocket engines, such spectra are potentially useful as a means of remotely monitoring rocket launches, especially in cases of unsuccessful launches where environmental hazards need to be assessed.